Greasing the path to BAX/BAK activation - MARTIN, SEAMUS (My University, 2012)
BAX/BAK activation leading to mitochondrial outer-membrane permeabilization is a key commitment point in apoptosis. Chipuk et al. now identify two sphingolipids as specific cofactors for BAX/BAK activation that lower the threshold for apoptosis-associated cytochrome c release. Association of mitochondria with other cellular membrane compartments is required for BAK/BAX exposure to these sphingolipids.
PUBLISHED
Keywords: BAX/BAK; BAX/BAK; Immunology, Inflammation & Infection